New Algorithms for Macromolecular Simulation - Leimkuhler, Benedict; Chipot, Christophe; Elber, Ron; Laaksonen, Aatto; Mark, Alan; Schlick, Tamar; Schütte, Christoph; Skeel, Robert (Lecture Notes in Computational Science and Engineering, 2006)
Molecular simulation is a widely used tool in biology, chemistry, physics and engineering. This book contains a collection of articles by leading researchers who are developing new methods for molecular modelling and simulation. Topics addressed here include: multiscale formulations for biomolecular modelling, such as quantum-classical methods and advanced solvation techniques; protein folding methods and schemes for sampling complex landscapes; membrane simulations; free energy calculation; and techniques for improving ergodicity. The book is meant to be useful for practitioners in the simulation community and for those new to molecular simulation who require a broad introduction to the state of the art.